Torneträsk tree-ring width (TRW) and density (MXD) AD 500-2004 - Grudd, Håkan (Stockholm University, 2019)
Tree-ring width (TRW) and maximum density (MXD) from Tornetrask in northern Sweden, covering the period AD 500 - 2004. Non-climatological growth trends in the data are removed using Regional Curve Standardization (RCS). A climate reconstruction based on MXD captures 63-64% of the inter-annual summer temperature variation.

Variables:
MXDrcs = Maximum ring density, with regional curve standardization
MXDlow = Low frequency (c. 100 yrs) variation,with 95% confidence interval
TRWrcs = Tree-ring width, with regional curve standardization
TRWlow = Low frequency (c. 100 yrs) variation,with 95% confidence interval

Torneträsk trädringbredd (TRW) och densitet (MXD) AD 500-2004.

Se engelska katalogsidan för utförligare beskrivning: https://snd.gu.se/en/catalogue/study/ECDS0182

Variabler:
MXDrcs = Maximum ring density, with regional curve standardization
MXDlow = Low frequency (c. 100 yrs) variation,with 95% confidence interval
TRWrcs = Tree-ring width, with regional curve standardization
TRWlow = Low frequency (c. 100 yrs) variation,with 95% confidence interval
Torneträsk trädringbredd (TRW) och densitet (MXD) AD 500-2004
Keywords: PALEOCLIMATE; TREE RINGS; PALEOCLIMATE RECONSTRUCTIONS; PALEOCLIMATE INDICATORS; palaeoclimatology; paleoklimatologi; Atmospheric conditions; Atmosfäriska förhållanden; Climate Science; Klimatvetenskap; Physical Geography; Naturgeografi; Climatology / Meteorology / Atmosphere; Klimatologi och meteorologi